Does that look heavy to you? Perceived weight judgment in lifting actions in younger and older adults - Maguinness, Corrina; Setti, Annalisa; Roudaia, Eugenie; Kenny, Rose Anne (Frontiers in Human Neuroscience, 2013)
When interpreting other people's movements or actions, observers may not only rely on the visual cues available in the observed movement, but they may also be able to “put themselves in the other person's shoes” by engaging brain systems involved in both “mentalizing” and motor simulation. The ageing process brings changes in both perceptual and motor abilities, yet little is known about how these changes may affect the ability to accurately interpret other people's actions. Here we investigated the effect of ageing on the ability to discriminate the weight of objects based on the movements of actors lifting these objects. Stimuli consisted of videos of an actor lifting a small box weighing 0.05–0.9 kg or a large box weighting 3–18 kg. In a four-alternative forced-choice task, younger and older participants reported the perceived weight of the box in each video. Overall, older participants were less sensitive than younger participants in discriminating the perceived weight of lifted boxes, an effect that was especially pronounced in the small box condition. Weight discrimination performance was better for the large box compared to the small box in both groups, due to greater saliency of the visual cues in this condition. These results suggest that older adults may require more salient visual cues to interpret the actions of others accurately. We discuss the potential contribution of age-related changes in visual and motor function on the observed effects and suggest that older adults' decline in the sensitivity to subtle visual cues may lead to greater reliance on visual analysis of the observed scene and its semantic context.